Meat Consumption Behaviour in Western Province, Sri Lanka: Drivers, Trends, and Future Outlook - Kumari, M.K.D.; Kumari, M.A.A.P. (University of Jaffna, 2025)
Understanding consumer behaviour related to meat consumption and attitudes towards the different meat types offers valuable insights for local producers and potential investors. Therefore, this study aimed to explore meat consumption behaviour among consumers in Western Province, Sri Lanka, and identify current patterns and attitudes towards different meat types. A pre-tested structured questionnaire was used to collect socio-demographic information, and meat consumption behaviour and attitudes towards the different meat types from a stratified sample of 395 respondents across Colombo, Gamapaha and Kaluthara during June to August 2024. The data were analyzed using descriptive and selected non-parametric tests. The sample was predominantly female respondents (67.8%), with the majority in the age group of 21-30 years (53.41%) and 46.45% living in semi-urban areas. The majority of respondents (88.57%) preferred chicken, followed by beef (5.82%), pork (5.06%) and mutton (3.54%), consuming it 2-3 times weekly and purchasing 0.5 to 1 kg (51.39%) of fresh meat from meat shops (68.1%). Additionally, 83.04% consumed processed meat products, with sausages (63.41%) being popular due to their ease of cooking (35.38%). A significant correlation (p<0.05) was found between the type of meat consumed and gender, age, occupation, and religion. Meat consumption frequency, amount purchased at one time, and market choice were also found to have significant differences (p<0.05) across the demographics. While many perceive chicken meat to contain antibiotics, harmful substances, and hormones, its affordability, versatility and cultural significance often outweigh these concerns. Higher costs limit the consumption of beef and mutton. The consumer preferences in the Western Province are driven by affordability, cultural norms, and perceived safety. Chicken dominates the market, while demand for other meats remains limited by cost. These patterns offer clear opportunities for targeted investment, consumer education, and development of safer, value-added meat products to better align with evolving consumer expectations.
Keywords: Consumer; Meat types; Preference; Sri Lanka